A Leishmania hypothetical protein-containing liposome-based formulation is highly immunogenic and induces protection against visceral leishmaniasis. (November 2018) - Ribeiro, Patrícia A.F.; Dias, Daniel S.; Novais, Marcus V.M.; Lage, Daniela P.; Tavares, Grasiele S.V.; Mendonça, Débora V.C.; Oliveira, Jamil S.; Chávez-Fumagalli, Miguel A.; Roatt, Bruno M.; Duarte, Mariana C.; Menezes-Souza, Daniel; Ludolf, Fernanda; et al.
Graphical abstract: Highlights: Vaccination to protect against visceral leishmaniasis is desirable. The most of proteins tested as vaccine candidates are poor immunogenic. There are few licensed and effective adjuvants on the market today. A recombinant Leishmania protein was associated with liposomes as adjuvants. The combination was immunogenic and protective against L. infantum infection in mice. Abstract: Leishmania proteins have been evaluated as vaccine candidates against leishmaniasis; however, most antigens present low immunogenicity and need to be added with immune adjuvants. A low number of licensed adjuvants exist on the market today; therefore, research conducted to produce new products is desirable. The present study sought to evaluate the immunogenicity and protective efficacy of a recombinant Leishmania hypothetical protein, namely LiHyR, administered with saponin or liposomes in BALB/c mice. Immunological and parasitological parameters were evaluated, and results showed significant protection against Leishmania infantum infection produced by both compositions in the immunized animals; however, this was not identified when the antigen was used alone. In addition, the liposomal formulation was more effective in inducing a polarized Th1 response in the vaccinated animals, which was maintained after challenge and reflected by lower parasitism found in all evaluated organs when the limiting dilution technique and RT-PCR assay were employed. The protected animals showed higher levels of protein and parasite-specific IFN-γ IL-2, IL-12, GM-CSF, and TNF-α, which were evaluated by capture ELISA and flow cytometry, in addition to a higher production of anti-protein and anti-parasite IgG2a antibodies, both before and after challenge. The Lip/rLiHyR combination induced higher IFN-γ production through both CD4 + and CD8 + T cell subtypes. Results indicate the possibility of using the LiHyR, containing a liposomal formulation, as a vaccine candidate against visceral leishmaniasis.